Exploring the benefits of international government bond portfolio diversification strategies. Issue 1 (2nd January 2019) - Fletcher, Jonathan; Paudyal, Krishna; Santoso, Timbul
ABSTRACT: We use the Bayesian approach of Wang (1998) to examine the diversification benefits of investing in international government bonds. We find that no short-selling constraints substantially reduce but do not eliminate the diversification benefits when only investing in G7 government bonds with different maturities. There are significant diversification benefits when using the G7 bonds, an inflation-linked bond index, and emerging market bonds even in the presence of no short-selling constraints. The superior performance is driven by the emerging markets bonds. We also find that the diversification benefits vary across different economic states.